For girls only : making a case for single-sex schooling - Streitmatter, Janice, 1952- (Albany : State University of New York Press, 1999)
For Girls Only examines research and public policy regarding single-sex schooling, especially girls-only classes in public, coeducational schools. Since the passage of Title IX in 1972, which calls for equal access and participation regardless of gender, educators have attempted to address gender equity issues in schools. Current research on the progress of female students in U.S. public schools suggests that efforts have not sufficiently addressed concerns such as academic under-achievement in the areas of math and science, lower self-esteem from the advent of early adolescence, and vulnerability to sexual harassment.
Despite Title IX, some educators have turned to the creation of single-sex classes and programs for female students in order to better address these critical issues. This book examines the longitudinal results of one study, reviews other research, and considers policy implications in conflict with Title IX.
1 On-Site Search for Gender Equity 1 -- 2 Public Policy versus Local Practice 11 -- 3 A Brief History of Girls-Only Schooling 25 -- 4 Recent Research on Single-Sex Schooling 35 -- 5 Profiles of the Schools, Teachers, and Classes 57 -- 6 Voices of the Teachers 67 -- 7 Voices of Girls in the Private School 81 -- 8 Voices of Girls in Public Coeducational Schools 89 -- 9 Taking a Step beyond Title IX 107.
Includes bibliographical references (pages 145-151) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Single-sex schools -- United States; Women -- Education -- United States; Educational equalization -- United States; Écoles non mixtes -- États-Unis.; Femmes -- Éducation -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; EDUCATION -- Elementary; Educational equalization; Single-sex schools; Women -- Education; United States; Mädchenbildung; Mädchenschule; Pädagogik; UNITED STATES